Influence of Rootstocks (Gisela 5, Gisela 6, MaxMa, SL 64) on Performance of ‘0900 Ziraat’ Sweet Cherry - Erdal Aglar; Kenan Yıldız (Journal of Basic & Applied Sciences, 2021)
This study was carried out in order to determine the effect of rootstocks (Gisela 5, Gisela 6, MaxMa 14 and SL 64) on performance of sweet cherry cultivar ‘0 900 Ziraat’ during 2010-2013 years. The trail in randomized block design was established as to factorial design. Each graft combination included 20 trees. The trees was trained as Spanish Bush training system. At the end of study, effect of rootstocks on vegetative growth was found significant. It has been determined that the trees grafted on SL 64 and MaxMa 14 rootstocks were more vigorous than the those grafted on Gisela 5 and Gisela 6. The rootstocks formed significant differences at the precocity. While the first blooming on the trees grafted on Gisela 5 and Gisela 6 rootstocks occurred at the second year after planting, the first blooming on the trees on MaxMa 14 and SL 64 rootstocks occurred at fourth year after planting. It has been determined that occur significant differences on yield per tree and yield efficiency among rootstocks. In terms of yield per tree and yield efficiency, While the lowest value was in SL 64 rootstock, the highest value was recorded in Gisela 5, and it has been determined that the differences between three rootstocks (Gisela 5, Gisela 6 and MaxMa 14) were not significant. While fruits weight varied according to the rootstock used in study, the trees grafted on Gisela 5 had the smallest fruit. Accompanied with differences between MaxMa 14 and SL 64 rootstocks were not significant, the biggest fruits were produced on trees grafted on SL 64 rootstock. As a result of the statistical analysis, it has determined that the rootstocks that used in trial did not create significant differences on soluble solids content (SSC) value. One of the most significant diagnosis was 6 % mortality rate that occurred on trees grafted Gisela 5 and Gisela 6 rootstocks.